Analysis of Teacher Preparedness for Using Technology in the Classroom Learning Process - Rahman, Priyanggo Karunia (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
The development of information and communication technology (ICT) has had a significant impact on several industries, particularly education. An obstacle that emerges is the preparedness of instructors to use technology in the educational process inside the formal classroom setting. Numerous studies have revealed that despite the rapid development of technology, not all teachers are well prepared to use it to its fullest potential. The objective of this study is to assess the preparedness of instructors to utilize technology in the classroom, pinpoint the obstacles they encounter, and propose remedies to enhance the efficacy of technical integration in the learning process. This study utilized a quantitative survey methodology, distributing a questionnaire to 100 teachers from various educational levels. Findings indicate that the majority of instructors have access to technology, but just 45% possess the necessary confidence in its use. Insufficient training, inadequate supporting infrastructure in schools, and a lack of familiarity with technological applications in the curriculum are the primary obstacles identified. These results suggest that instructors need ongoing training and adequate infrastructure to improve their technology readiness. Therefore, it is possible to integrate technology into the education process more efficiently and in line with the demands of modern education.